Potassium Starvation Limits Soybean Growth More than the Photosynthetic Processes across CO2 Levels - Singh, Shardendu K.; Reddy, Vangimalla R. (Frontiers in Plant Science, 2017)
Elevated carbon dioxide (eCO2) often enhances plant photosynthesis, growth, and productivity. However, under nutrient-limited conditions the beneficial effects of high CO2 are often diminished. To evaluate the combined effects of potassium (K) deficiency and eCO2 on soybean photosynthesis, growth, biomass partitioning, and yields, plants were grown under controlled environment conditions with an adequate (control, 5.0 mM) and two deficient (0.50 and 0.02 mM) levels of K under ambient CO2 (aCO2; 400 µmol mol-1) and eCO2 (800 µmol mol-1). Results showed that K deficiency limited soybean growth traits more than photosynthetic processes. An approximately 54% reduction in leaf K concentration under 0.5 mM K versus the control caused about 45% less leaf area, biomass, and yield without decreasing photosynthetic rate (Pnet). In fact, the steady photochemical quenching, efficiency, and quantum yield of photosystem II, chlorophyll concentration (TChl), and stomatal conductance under 0.5 mM K supported the stable Pnet. Biomass decline was primarily attributed to the reduced plant size and leaf area, and decreased pod numbers and seed yield in K-deficient plants. Under severe K deficiency (0.02 mM K), photosynthetic processes declined concomitantly with growth and productivity. Increased specific leaf weight, biomass partitioning to the leaves, decreased photochemical quenching and TChl, and smaller plant size to reduce the nutrient demands appeared to be the means by which plants adjusted to the severe K starvation. Increased K utilization efficiency indicated the ability of K-deficient plants to better utilize the tissue-available K for biomass accumulation, except under severe K starvation. The enhancement of soybean growth by eCO2 was dependent on the levels of K, leading to a K × CO2 interaction for traits such as leaf area, biomass, and yield. A lack of eCO2-mediated growth and photosynthesis stimulation under severe K deficiency underscored the importance of optimum K fertilization for maximum crop productivity under eCO2. Thus, eCO2 compensated, at least partially, for the reduced soybean growth and seed yield under 0.5 mM K supply, but severe K deficiency completely suppressed the eCO2-enhanced seed yield.